1989
DOI: 10.1007/bf00442257
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of amphetamine, apomorphine and white noise on response switching in the rat

Abstract: The effects of d-amphetamine, apomorphine and white noise on response switching in the rat were examined using a schedule of reinforcement which resulted in the subjects displaying a range of different probabilities of switching. The procedure was analogous to the use of a fixed interval schedule of reinforcement for examining the rate-dependent effects of drugs. d-Amphetamine (0.4-4.0 mg/kg) increased response switching in a manner dependent both upon the dose of drug and the baseline probability of switching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A further possibility is that the deficits observed in experiments 1 and 2 occurred as a result of the effects of Damphetamine on task switching (Robbins and Evenden 1984;Evenden and Dogget 1989), rather than any detrimental effects on conditional discrimination per se. However, direct analysis of this possibility in experiment 1 rejected this account.…”
Section: Discussionmentioning
confidence: 99%
“…A further possibility is that the deficits observed in experiments 1 and 2 occurred as a result of the effects of Damphetamine on task switching (Robbins and Evenden 1984;Evenden and Dogget 1989), rather than any detrimental effects on conditional discrimination per se. However, direct analysis of this possibility in experiment 1 rejected this account.…”
Section: Discussionmentioning
confidence: 99%
“…In the FR-Switch procedure, the effects of amphetamine were similar to published data in this dose range. Evenden and Doggett (1989) found dose-dependent increases in switching of about the same magnitude, with no effect on average response rate. The second psychomotor stimulant tested was caffeine, which increased switching in both procedures at 30 mg/kg.…”
Section: Discussionmentioning
confidence: 75%
“…In the second, explicit reinforcement is provided for the first switch made after the completion of 21 responses [fixed ratio (FR) 21], which can be distributed over the two levers without restriction (FR-switch). During training, a pattern develops in which the subjects tend to repeat responses at the beginning of the FR21, but to switch between the two levers with greater frequency as the FR progresses, generating a variety of baseline probabilities of switching in each session for each individual subject (Evenden 1986;Evenden and Doggett 1989). Robbins and Watson (1981) found that amphetamine reduced the probability of repeating responses (an increase in switching).…”
Section: Introductionmentioning
confidence: 99%